A highly dispersible silica pH nanosensor with expanded measurement ranges1. (2nd June 2015) - Hu, Shuchao; Sun, Ling; Liu, Mingxing; Zhu, Hongda; Guo, Huiling; Sun, Hongmei; Sun, Honghao
<x xml:space="preserve">Abstract</x> Two kinds of silica based colloidal ratiometric fluorescent pH sensors were successfully developed. The measurement range was expanded to almost 4 pH units.